Sustainable management of sediment resources. - Owens, Philip N. (Philip Neil), 1966- (Sustainable management of sediment resources., 2008)
Sediments are a natural part of aquatic systems & they are essential for the hydrological, geomorphological & ecological functioning of those systems. However, due to the ever increasing use of river catchments, sediments need to be managed in a balanced & sustainable way. This book covers this topic.